2019
DOI: 10.1007/s11302-019-09653-6
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine stimulation of P2Y1 receptors is part of the purinergic signaling mechanism that regulates T cell activation

Abstract: Previous studies have shown that T cell receptor (TCR) and CD28 coreceptor stimulation involves rapid ATP release, autocrine purinergic feedback via P2X receptors, and mitochondrial ATP synthesis that promote T cell activation. Here, we show that ADP formation and autocrine stimulation of P2Y1 receptors are also involved in these purinergic signaling mechanisms. Primary human CD4 T cells and the human Jurkat CD4 T cell line express P2Y1 receptors. The expression of this receptor increases following T cell stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
(73 reference statements)
1
13
0
Order By: Relevance
“…In order to study whether P2Y11 receptors are involved in Ca 2+ signaling during T cell stimulation, we loaded human CD4 cells with the cytosolic Ca 2+ probe Fluo-4 AM that allows real-time monitoring of intracellular Ca 2+ levels using live-cell fluorescence microscopy. In agreement with previous reports,18,33 we found that inhibition of P2X4 receptors completely abolished the Ca 2+ signaling response to cell stimulation by TCR/CD28 crosslinking (Fig. 2A, B).…”
supporting
confidence: 93%
“…In order to study whether P2Y11 receptors are involved in Ca 2+ signaling during T cell stimulation, we loaded human CD4 cells with the cytosolic Ca 2+ probe Fluo-4 AM that allows real-time monitoring of intracellular Ca 2+ levels using live-cell fluorescence microscopy. In agreement with previous reports,18,33 we found that inhibition of P2X4 receptors completely abolished the Ca 2+ signaling response to cell stimulation by TCR/CD28 crosslinking (Fig. 2A, B).…”
supporting
confidence: 93%
“…Recently, Woehrle T et al found that P2Y1R could regulate T cell function. It found that exogenous ADP or overexpression of P2Y1R could dramatically increase mRNA transcription of IL-2 in response to TCR/CD28 stimulation, and antagonists or silencing of P2Y1R could reduce mRNA transcription of IL-2 and mitochondrial Ca 2+ uptake in stimulated CD4 + T cells (15). However, the role of P2Y1R in regulation of adaptive immunity still remains largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…P2Y1R is a Gα q/11 ADP receptor, which is abundant in nearly all human and rodent tissues ( 14 ). Besides its key role in the nervous system, P2Y1R also exerts potent immunity such as leading NLRP3 inflammasome priming and facilitating T cell activation in an ERK-dependent manner ( 13 , 15 ). However, its function in regulation of Th17 cells is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies will be required to determine the precise mechanism by which IVM modulates P2Y1 activity. One possibility is that IVM may augment P2X-P2Y1 crosstalk to drive insulin secretion, which has been shown to drive Ca 2+ and P2Y1-dependent activation of other cell types (52,63).…”
Section: Discussionmentioning
confidence: 99%